Analyzing the Role of Technological Capabilities and Digital Marketing on the Performance of E-Commerce-Based SMEs - Mittal, Saurabh; Kumar, Vikas (Indian Journal of Marketing, 2024)
Purpose : The research study aimed to analyze the impact of digital marketing and technological capabilities on the financial and operational efficiency of e-commerce-based small and medium-sized enterprises (SMEs) in India. The organizations spending their marketing budgets on digital marketing platforms plan to get more efficiency and cost optimization with their campaigns. Such optimization may be crucial, particularly for small and medium-sized businesses that rely on e-commerce. The goal of the study was to determine how contemporary SMEs may enhance their performance by utilizing advanced technology, growing smartphone usage, and improving technical competence. Methodology : A theoretical framework was proposed, premised on the substantial impact of digital marketing and technological capabilities on SMEs’ performance. Empirical data was collected from SME executives in India. The data was analyzed using factor analysis and regression techniques to assess the impact on the performance of these e-commerce-based SMEs. Findings : The analysis revealed the significant role of technological capabilities and digital marketing in enhancing the financial and operational performance of e-commerce-based SMEs in India. Practical Implications : The study provided managerial insights into how SMEs can effectively harness digital marketing and technological capabilities to improve their operational efficiency and financial outcomes. The findings suggested strategies for SMEs to adapt to dynamic customer expectations and increased competition in the digital marketplace. Originality : The research contributed to the existing literature by developing a theoretical model that links digital marketing and technological capabilities to the performance of e-commerce-based SMEs in a developing country, specifically India.